2014
DOI: 10.32007/jfacmedbagdad.563497
|View full text |Cite
|
Sign up to set email alerts
|

Spiro metric Tests and Thyroid Hormone Concentrations in sample of Iraqi Patients with Chronic Obstructive Pulmonary Disease.

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a preventable disease with some significant extra pulmonary effects that may contribute to the severity in individual patients.. The systemic manifestations  of  COPD  include  a number of endocrine disorders , such  as  those  involving the pituitary, the thyroid , the gonads, the adrenals  and  the pancreas.  The  mechanisms  by which COPD  alters  endocrine function are incompletely understood  but likely involve  hypoxemia , hypercapnia , systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Patients with COPD had a higher prevalence of T2DM, hypertension, atherosclerotic cardiovascular diseases, and dyslipidemia than the control group. While data on the epidemiology of COPD and its comorbidities in Iraq is limited, some studies have reported increased gastroesophageal reflux symptoms among Iraqi COPD patients, with no association found with thyroid dysfunction or fibromyalgia [ 14 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with COPD had a higher prevalence of T2DM, hypertension, atherosclerotic cardiovascular diseases, and dyslipidemia than the control group. While data on the epidemiology of COPD and its comorbidities in Iraq is limited, some studies have reported increased gastroesophageal reflux symptoms among Iraqi COPD patients, with no association found with thyroid dysfunction or fibromyalgia [ 14 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism is either thyroid dysgenesis or dyshormogenesis (4)(5)(6). Reduction in circulating thyroid hormones slows cell metabolism and growth (7,8); memory impairment, and neurological disorder in dogs (9). Hypothyroidism reduces the health-related quality of life in addition to depression and mood disturbances (10).…”
Section: Introductionmentioning
confidence: 99%